Understanding Formal and Informal English: A Literature Review - Habib Anugerah Alkarim; Angela Surya Ginting; Dona Aisyah Sitorus; Naylatul Fadhilah Ginting; Munawarah br. Limbong; Deasy Yunita Siregar (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This literature review examines the use and characteristics of formal and informal English in a range of contexts, including digital communication, classroom interaction, and academic writing. Based on five selected studies, the review analyzes differences between formal and informal registers in terms of vocabulary choice, sentence structure, and pragmatic functions.The first study explores language use in digital communication, emphasizing how context and social conventions influence register selection. The second and fourth studies investigate classroom settings, focusing on how students and lecturers employ both formal and informal expressions in English language learning. The third study offers a theoretical discussion of linguistic features that distinguish formal and informal registers, providing a foundation for understanding register variation. The fifth study examines the use of formal and informal language in academic writing, highlighting the difficulties learners face in applying appropriate registers. Overall, the review highlights the importance of understanding register differences for effective communication, language education, and teaching practices, and emphasizes the need for pedagogical approaches that promote register awareness in diverse learning contexts.